Rapid determination of 103 common veterinary drug residues in milk and dairy products by ultra performance liquid chromatography tandem mass spectrometry - Guo, Xiujuan; Tian, Hao; Yang, Fan; Fan, Sufang; Zhang, Jingwen; Ma, Junmei; Ai, Lianfeng; Zhang, Yan (Frontiers in Nutrition, 2022)
A multi-residue method has been developed for the identification and quantification of 103 common veterinary drug residues in Milk and Dairy Products. This method was based on QuEChERS with dispersive solid-phase where C18 sorbent and anhydrous sodium sulfate were used to sample purification. After evaporation and reconstitution, the samples were analyzed by ultra-performance liquid chromatography-tandem mass spectrometry. The mean recovery results were all higher than 60% except ampicillin, pipemidic acid, enoxacin, and estriol, and the relative standard deviation was less than 20.0%. The limit of quantification ranged between 0.1 and 5 μg/kg for milk and between 0.5 and 25 μg/kg for milk powder. It was successfully used to detect residues of veterinary drug in real samples. This study proposes a simple and fast analytical method for monitoring multi-class veterinary drug residues to ensure food safety.